Dairy, dairy, quite contrary - Lillard, Amy (Lillard, Amy. Sunflower Café mysteries., 2022)
"Looking for a fresh start, advice columnist Sissy Yoder heads to small-town Yoder, Kansas, to help in her aunt's café. But when a milkman is murdered, the newcomer becomes the prime suspect . . . After Sissy's rodeo cowboy boyfriend turns out to be more of a rodeo clown, she packs a bag; picks up her Yorkshire terrier Duke; and leaves Tulsa, Oklahoma, bound for her parents' former hometown. There are still plenty of Yoders in Yoder, Kansas, including Sissy's aunt Bethel, who owns the Sunflower Café but recently broke her leg. It's a homecoming of sorts as Sissy arrives to help in the café and reunite with her pregnant cousin Lizzie. Plus she can continue to secretly write her newspaper advice column as seventy-year-old 'Aunt Bess.' But it's Sissy who could use some advice when she finds the milk deliveryman out behind the café with a knife in his back. As the sheriff's prime suspect, it's up to Sissy to catch the backstabber herself--before someone else gets creamed . . ."--Page 4 of cover.